The Effect of Varying Concentrations and Application Periods of Chondroitinase ABC on Tissue-Engineered Cartilage - Tong, Eric; O’Connell, Grace D.; Kelly, Terri-Ann N.; Hung, Clark T. (Columbia Undergraduate Research Journal, 2014)
Osteoarthritis, a chronic malady characterized by joint pain and swelling, is caused by damage to articular cartilage and is perpetuated by low-grade inflammation. Treatments for osteoarthritis do exist, but many treatments focus on coping with the disease rather than curing it. Surgical options that replace damaged cartilage tissue with that of donor cartilage tissue or cartilage tissue from other parts of articular joints face complications especially when the tissue is not of the correct size or does not have native-like properties. A more suitable treatment option for osteoarthritis is to develop an in vitro tissue-engineered cartilage construct that can be grown using the patient’s own cells and to surgically remove the patient’s damaged cartilage and replace it with the tissue-engineered cartilage. A challenge in developing such a treatment option is producing tissue-engineered cartilage with mechanical properties akin to those of native human articular cartilage. This challenge may be overcome by maximizing the production of type II collagen by the chondrocytes in vitro. One way to maximize collagen production is through the application of chondroitinase ABC, an enzyme which temporarily suppresses proteoglycans in the cartilage matrix to create more space for type II collagen to develop. In this study, two two levels of cABC treatment were applied (“high” and “low”) to cartilage tissue constructs. The “low” cABC treated group received daily feeding of 0.075 U/mL from day 14 to 21 followed by a replacement of chondrogenic media without cABC. The “high” cABC treated group received a single addition of 0.15 U/mL from day 14 to 16 followed by a replacement of chondrogenic media without cABC. At the end of 42 days, the constructs were subjected to mechanical testing and biochemical analyses. These analyses showed that the high cABC treatment yielded more native-like mechanical properties when compared to the low cABC treatment and the control results. Biochemical and histological analyses confirmed that the proteoglycan and collagen II content were higher in the low and high cABC treated groups when compared to the control. All analyses show that the most efficient application of chondroitinase ABC is through a two day duration treatment of a higher concentration (0.15 U/mL).